Excitation Energy Transfer Dynamics from Carotenoid to Bacteriochlorophyll a in the LH2 Complex of Rhodobacter sphaeroides: Insights from Reconstitution Experiments with Carotenoids and B800 Bacteriochlorophyll a - Uragami, Chiasa; Yoshida, Marina; Gardiner, Alastair T; Cogdell, Richard J; Hashimoto, Hideki (Molecules (Basel, Switzerland), 2025)
Carotenoids are crucial for photosynthesis, playing key roles in light harvesting and photoprotection. In this study, spheroidene and bacteriochlorophyll a (Bchl a) were reconstituted into the chromatophores of the carotenoidless mutant Rhodobacter sphaeroides R26.1, resulting in the preparation of high-quality LH2 complexes. Global and target analyses of transient absorption data revealed that incorporating B800 Bchl a significantly enhances excitation energy transfer (EET) efficiency from carotenoids to Bchl a. EET predominantly occurs from the carotenoid S2 state, with additional pathways from the S1 state observed in native LH2. Unique relaxation dynamics were identified, including the generation of the carotenoid S* state in reconstituted LH2 with both spheroidene and B800 Bchl a and the formation of the carotenoid T1 state in reconstituted LH2. These findings underscore the critical influence of pigment composition and spatial organization on energy transfer mechanisms. They provide valuable insights into the molecular interplay that governs excitation energy transfer in photosynthetic light-harvesting systems.
Keywords: fotosyntéza; Bacterial Proteins; carotenoid; Photosynthesis; Energy Transfer; Bacteriochlorophyll A; B800 bacteriochlorophyll a; purple photosynthetic bacteria; light-harvesting; reconstitution; přenos energie; Light-Harvesting Protein Complexes; Rhodobacter sphaeroides; Carotenoids; bakteriochlorofyl A; bakteriální proteiny; světlosběrné proteinové komplexy; photoprotection; karotenoidy